A comparison of DALYs for periodontal disease in China between 1990 and 2013: insights from the 2013 global burden of disease study - Qi Zhang; Zhixin Li; Chunxiao Wang; Yunning Liu; Yang Yang; Scottie Bussell; Maigeng Zhou; Linhong Wang (BMC Oral Health, 2017)
Abstract Background China has undergone a rapid demographic and epidemiological transition with fast ecomonic development since the 1980s. Oral health is becoming a major public health problem as the prevalence of non-communicable diseases has greatly increased. Periodontal disease (PD) and caries are among the most prevalent oral diseases. PD accounts for the majority of tooth loss and increases with age. China’s third national epidemiological investigation on oral diseases (2005) revealed that periodontitis affected >50% of the adult population. The Global Burden of Disease Study 2013 (GBD2013) have been used to estimate DALYs for 301 acute and chronic diseases and injuries in 188 countries for 1990–2013. The estimation of burden of PD between 1990 and 2013 will provide a unique perspective for planning interventions and developing public health policies for PD even chronic diseases in China. Methods We used the GBD 2013 results for Years of Life Lost (YLLs) and Years Lived with Disability (YLDs) to calculate Disability Adjusted Life Years (DALYs) for PD in China. PD standardized DALYs rate (SDR) per 100,000 persons, the percentage of PD standardized DALYs rate (% PD SDR) in all diseases DALYs, and variance ratio of these two indexes between the years of 1990 and 2013 were compared by province, gender and age groups. Results Nationwide, compared to 1990, the SDR in 2013 increased slightly from 24.7 to 25.7, while the variance ratio of SDR for provinces in the middle, west and south of China showed a greater variation(4.8–6.2%). The % PD SDR in all disease DALYs increased from 0.06 to 0.11% for all groups. The four highest variance ratios % PD SDR in all diseases DALYs between 1990 and 2013 occurred in the west of China (97, 98.6, 108.4 and 112.8%). The PD SDR changed slightly in the women (20.3 to 21.7), meanwhile the variance ratio of PD SDR and % PD SDR in all diseases DALYs for the women (6.7 and 94.5%) was also higher than for men (2.1 and 60.6%). The highest variance ratio % PD SDR in all oral diseases DALYs occurred between 1990 and 2013 in ages 20 to 24 (50.7%) and 25 to 29 years (50.5%). Conclusion The PD standardized DALYs rate and % PD SDR in all diseases DALYs in China in 2013 has increased from 1990. Especially, the variance ratio of % PD SDR in all disease DALYs among Young population and women, in the west provinces of China have been becoming the highest in all age groups and national wide. Future intervention measurements should include young women of child-bearing age because women’s health impacts infant health. Periodontal disease has risk factors in common with a number of other non-communicable diseases (NCD) and conditions, and focusing on the common behavioral and environmental risk factors would be instrumental in the effective prevention of periodontal disease.